2018
DOI: 10.14434/josotl.v18i4.22729
|View full text |Cite
|
Sign up to set email alerts
|

Flipping the Classroom: Effects on Course Experience, Academic Motivation, and Performance in an Undergraduate Exercise Science Research Methods Course

Abstract: The goal of the study was to determine the effects of the Flipped Classroom Model (FCM) on students’ course experience, basic need satisfaction, motivation, and academic performance in an undergraduate Research Methods course for exercise science majors. One section received instruction in a Traditional Lecture Model (TLM), while the other section received instruction via the FCM. An adapted survey was administered to approximately 175 students, with 83% responding. Significant differences were seen in course … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…In order to make the material available to the students, the instructors use different systems: printed documents, email, WhatsApp, Facebook, Youtube, Moodle, Google Classroom, Blackboard, ECHO360 software, and the Socrative platform. In relation to the research results, it can be seen in Table 5 that the majority of the studies found that IM had been developed following the FL pedagogical model and relied on the SDT, which supports the basic psychological needs required for the growth of autonomy, competence, and relatedness [10][11][12][13]21,22,[24][25][26]31,32,35,36]. In addition, some studies that have compared traditional FL and gamified FL have found better results with the later, since it encouraged students to participate in the learning process [23,37], while another study that did so perceived improvements only in IM and social relatedness [34].…”
Section: Zhao Et Al (2021) [37]mentioning
confidence: 74%
See 2 more Smart Citations
“…In order to make the material available to the students, the instructors use different systems: printed documents, email, WhatsApp, Facebook, Youtube, Moodle, Google Classroom, Blackboard, ECHO360 software, and the Socrative platform. In relation to the research results, it can be seen in Table 5 that the majority of the studies found that IM had been developed following the FL pedagogical model and relied on the SDT, which supports the basic psychological needs required for the growth of autonomy, competence, and relatedness [10][11][12][13]21,22,[24][25][26]31,32,35,36]. In addition, some studies that have compared traditional FL and gamified FL have found better results with the later, since it encouraged students to participate in the learning process [23,37], while another study that did so perceived improvements only in IM and social relatedness [34].…”
Section: Zhao Et Al (2021) [37]mentioning
confidence: 74%
“…Langdon and Sturges (2018) [31] Analyze the impact of FL on undergraduate students' academic performance, motivation, basic need satisfaction, and course experience.…”
Section: Spain 210mentioning
confidence: 99%
See 1 more Smart Citation
“…A higher score in each subscale, after reversing some items, indicates a more favorable situation of the person in that subscale. Cronbach's alpha coefficients for this scale have been reported from 0.85 to 0.94 (Langdon, Sturges, & Schlote, 2018). In a study among university students, Tanhaye Reshvanloo, Saeidi Rezvani, Samadiye, & Kareshki (in press) examined the psychometric properties of BNS-RS.…”
Section: Methodsmentioning
confidence: 99%
“…This scale measures autonomy, competence, and relatedness with nine items that answered in a 7-point Likert scale (1 = not at all true for me to 7 = very true for me). The reported Cronbach's alpha (α) coefficients for this scale range from .85 to .94 (Langdon et al, 2018). In a study conducted among Iranian students, Tanhaye Reshvanloo et al (2023) examined the psychometric properties of this scale.…”
Section: Basic Need Satisfaction In Relationships Scale (Bns-rs; La G...mentioning
confidence: 99%